A method for investigating the quality of evolving object‐oriented software using defects in global software development projects. Issue 8 (3rd May 2016) - Jabangwe, Ronald; Wohlin, Claes; Petersen, Kai; Šmite, Darja; Börstler, Jürgen
Abstract: Context: Global software development (GSD) projects can have distributed teams that work independently in different locations or team members that are dispersed. The various development settings in GSD can influence quality during product evolution. When evaluating quality using defects as a proxy, the development settings have to be taken into consideration. Objective: The aim is to provide a systematic method for supporting investigations of the implication of GSD contexts on defect data as a proxy for quality. Method: A method engineering approach was used to incrementally develop the proposed method. This was done through applying the method in multiple industrial contexts and then using lessons learned to refine and improve the method after application. Results: A measurement instrument and visualization was proposed incorporating an understanding of the release history and understanding of GSD contexts. Conclusion: The method can help with making accurate inferences about development settings because it includes details on collecting and aggregating data at a level that matches the development setting in a GSD context and involves practitioners at various phases of the investigation. Finally, the information that is produced from following the method can help practitioners make informed decisions when planning to develop software in comparable circumstances. Copyright © 2016 John Wiley & Sons, Ltd.